Suspected Hepadnavirus Association with a Hepatocellular Carcinoma in a Black-Tailed Prairie Dog (Cynomys ludovicianus). Issue 4 (November 2017) - Wright, T.L.; Eshar, D.; Carpenter, J.W.; Lin, D.; Padmanabhan, A.; Peddireddi, L.; Cino, G.
Summary: Hepatocellular carcinomas are the most commonly reported neoplasm of black-tailed prairie dogs ( Cynomys ludovicianus ). In several other closely related Sciuridae species, infection with species-specific hepadnaviruses is associated with the development of these tumours, but such a hepadnavirus has not yet been identified in any prairie dog species, although its presence has been hypothesized previously. An adult prairie dog was humanely destroyed due to progressive illness and the identification of a cranial abdominal mass that was determined on histopathology to be a hepatocellular carcinoma. Deep sequencing of the tumour tissue identified the presence of a hepadnavirus, similar in its genetic structure to woodchuck hepatitis virus. Electron microscopy showed the presence of viral particles similar in structure to other hepadnaviral particles. This report suggests that a hepadnavirus may be associated with the development of hepatocellular carcinomas in the prairie dog.